International expansion plan of Softfinaça to Uae - Sharma, Yash Yamdagni (2022)
The following document answers where Soft Finança (SF), a Portuguese software development company, should expand its product, “Soft Payments.”To truly identify a suitable market, the report conducts an internal and market assessment to understand the firm’s current situation and potential. An individual in-depth analysis then analyses the viability of the company entering the UAE. With this information, a joint venture expansion into Luxembourg was identified as having the highest potential for SF, while a marketing analysis found that targeting affluent families would lead to the highest returns